Increasing oilseed production through cluster demonstration in Patna district: A case study - Binita Rani; Rajeev Kumar; Prakash Chandra Gupta (Journal of Oilseed Brassica, 2026)
Cluster Frontline Demonstration was conducted to study the impact of improved cultivar, seed treatment, sulphurapplication, diseases and pest management on production as well as productivity of linseed and mustard. Resultsrevealed that Shekhar variety of linseed performed better as compared to local variety with 28.6 % yield gap betweenboth the varieties. Similarly, RNG-48 of Indian mustrad recorded 32.0 % higher seed yield compared to local variety.Therefore, the results clearly indicates that the use of improved varieties with scientific package and practices underCluster Frontline Demonstration programme can play a key role in improving the seed yield of oilseeds and will significantlycontribute to increase the productivity of oilseeds in Bihar state.